Lymphocele: a possible relationship with acute cellular rejection in kidney transplantation - Lipay, Marco Aurélio Silva; Noronha, Irene de Lourdes; Vidonho Júnior, Armando; Romão Júnior, João Egídio; Campagnari, João Carlos; Srougi, Miguel (São Paulo Medical Journal, 1999)
CONTEXT: The incidence of lymphocele after renal transplantation varies between 0.6 and 18% of cases, and many factors have been associated to its etiology. Cellular rejection of the kidney allograft has been described as a possible causal factor of lymphocele. OBJECTIVE: To analyze the possible relationship between lymphocele and acute cellular rejection. DESIGN: A retrospective study. SETTING: A referral hospital center. SAMPLE: 170 patients submitted to kidney transplantation from March 1992 to January 1997. A standard technique for renal transplantation was used. RESULTS: Of the 19 patients that developed lymphocele, 16 presented at least one episode of acute cell rejection (84%), and were treated with methylprednisolone. The relation between lymphocele and rejection was statistically significant (p = 0.04). Treatment of lymphocele consisted of peritoneal marsupialization in 3 patients (15.3%), percutaneous drainage in 7 (36.8%), laparascopic marsupialization in 2 (10.5%), and conservative treatment in 7 patients (36.8%). Evolution was favorable in 15 patients (78.9%), 1 patient (5.3%) died due to a cause unrelated to lymphocele, and 3 (15.8%) lost the graft due to immunological factors. The average follow-up period was 24.5 months. CONCLUSION: The high incidence of acute cell rejection in patients with lymphocele suggests a possible causal relationship between both conditions.